Heat Wave–Associated Vibriosis, Sweden and Finland, 2014 - Triñanes Fernández, Joaquín Ángel; Baker-Austin, Craig; Salmenlinna, Sara; Löfdahl, Margareta; Taylor, Nick G.H.; Martínez Urtaza, Jaime Luis (Emerging Infectious Diseases)
During summer 2014, a total of 89 Vibrio infections were reported in Sweden and Finland, substantially more yearly infections than previously have been reported in northern Europe. Infections were spread across most coastal counties of Sweden and Finland, but unusually, numerous infections were reported in subarctic regions; cases were reported as far north as 65°N, ≈100 miles (160 km) from the Arctic Circle. Most infections were caused by non-O1/O139 V. cholerae (70 cases, corresponding to 77% of the total, all strains were negative for the cholera toxin gene). An extreme heat wave in northern Scandinavia during summer 2014 led to unprecedented high sea surface temperatures, which appear to have been responsible for the emergence of Vibrio bacteria at these latitudes. The emergence of vibriosis in high-latitude regions requires improved diagnostic detection and clinical awareness of these emerging pathogens SI